1998
DOI: 10.1590/s1415-790x1998000100006
|View full text |Cite
|
Sign up to set email alerts
|

Incidência e fatores de risco para tuberculose em Pelotas, uma cidade do Sul do Brasil

Abstract: Objetivou-se medir a incidência e avaliar fatores de risco para tuberculose, em adultos de Pelotas. Os casos foram detectados na "Secretaria Municipal da Saúde e Bem Estar" (Centro de Saúde), no período de junho de 1994 a junho de 1995. Concomitante, controles populacionais, pareados por sexo e idade, eram sorteados e aplicado o mesmo questionário aos casos e controles. A incidência notificada de tuberculose foi de 72,4/100.000 habitantes. A análise estatística bruta mostrou os seguintes odds ratios: 10,8 (cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
(12 reference statements)
1
14
0
7
Order By: Relevance
“…However, the proportion of tuberculosis patients co-infected with HIV is 20.3%, which is higher than the 15.0% reported for Brazil as a whole. (5,6) The proportion of tuberculosis patients co-infected with HIV found in the present study (i.e., 50.0%) is in agreement with the findings of another group of researchers, (7) who reported that proportion to be 48.9% among inpatients at hospitals in southern Brazil. The fact that the proportion of HIV-positive individuals among patients hospitalized with tuberculosis is higher than is that of those among all of the reported cases of tuberculosis might denote greater disease severity in that group or reflect the trend toward hospitalization at referral hospitals for the treatment of infectious and parasitic diseases.…”
Section: Discussionsupporting
confidence: 93%
“…However, the proportion of tuberculosis patients co-infected with HIV is 20.3%, which is higher than the 15.0% reported for Brazil as a whole. (5,6) The proportion of tuberculosis patients co-infected with HIV found in the present study (i.e., 50.0%) is in agreement with the findings of another group of researchers, (7) who reported that proportion to be 48.9% among inpatients at hospitals in southern Brazil. The fact that the proportion of HIV-positive individuals among patients hospitalized with tuberculosis is higher than is that of those among all of the reported cases of tuberculosis might denote greater disease severity in that group or reflect the trend toward hospitalization at referral hospitals for the treatment of infectious and parasitic diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Alcoholism, which the current study found to be associated with treatment failure and the combined negatives outcomes, is a classical factor 12,13 both for developing TB 24 and for poor treatment outcome.…”
Section: Discussionmentioning
confidence: 62%
“…9 With the decentralization of the TB control actions to the primary care services in 2004, and also with the adoption of the DOTS strategy, the Brazilian PNCT recognizes the importance of extending the fight against TB to all the healthcare services of SUS. Therefore, it aims at the integration between TB control and the primary care services, including PSF in order to ensure the effective expansion of the access to diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%